Optimising standards of care of heart failure in general practice the OSCAR-HF pilot study protocol. Issue 5 (3rd September 2019) - Smeets, Miek; Aertgeerts, Bert; Mullens, Wilfried; Penders, Joris; Vercammen, Jan; Janssens, Stefan; Vaes, Bert
Abstract: Background: Heart failure (HF) imposes a burden for patients and health economics. General practitioners (GPs) are confronted with the broadest range of HF management. Although guidelines exist, they are not fully implemented in the Belgian health care system. Methods: We will conduct a non-randomised, non-controlled prospective observational trial (six months follow-up) to implement a multifaceted intervention in Belgian general practice to support GPs in the implementation of evidence-based HF guidelines. The multifaceted intervention consists of an audit and feedback method to detect previously unrecognised patients with HF and to increase awareness for proactive HF management, an NT-proBNP point-of-care test to improve detection and adequate diagnosis of patients with HF and a specialist HF nurse to assist GPs in the education of patients, optimisation of treatment and follow-up after hospitalisation. All patients aged 40 years and older with a confirmed diagnosis of HF by their GP based on the clinical audit are eligible for participation. The main objective of this pilot study is to evaluate the feasibility of this multifaceted intervention and the evolution of predefined quality indicators. We will measure the impact on HF diagnosis, medication optimisation, multidisciplinary follow-up and patients' quality of life after six months. Additionally, the experiences of GPs and investigators will be studied. Conclusions: Heart failure is an important health problem in which GPs play a key role. Therefore, we will evaluate the feasibility of a multifaceted intervention to optimise diagnosis as well as implement the guideline recommended therapies in patients with HF in general practice.